Enhancing Women’s Participation and Advancement in Competitive Cycling - Marlene A. Dixon; Jeffrey A. Graham; Allyson C. Hartzell; Katherine Forrest (Journal of Applied Sports Management, 2017)
While male participation in competitive cycling in the United States has grown tremendously, a lack of growth in female participation indicates there are discouraging factors at play. Critical examination of sport organizations can reveal structures and policies that exclude women from full participation. This study critically examines USA Cycling’s racing structure and policies with the goal of identifying exclusionary practices that might reduce women’s participation and advancement in competitive cycling. Using multiple data sources, including interviews with 10 competitive female cyclists, this study revealed multiple practices that strongly discourage women’s advanced participation in competitive cycling. Suggestions for practice are offered. Subscribe to JASM
Keywords: Women in sport; sport development; sport governance; USA Cycling